The Roles of Labour Union in Nigeria Industrial Harmony and Development - Onyebuchi, Obiekwe; Lucky, Obibhunun (International Journal of Sustainable Development & World Policy, 2019)
This paper examined the roles of labour union in Nigeria industrial harmony and development. It notes that strong and united labour unions are pre-requisites to industrial and national development of any nation. Some objectives of trade unions such as negotiation, representative body, maintenance of employee-employer relationship, and promotion of member’s welfares were noted and discussed. The paper also observed that workers join union because of job security, need for adequate wages and benefits, power in group for collective bargaining and need to associate with others. Some challenges facing labour unions in Nigeria such as disunity, financial weakness, weak collective bargaining process and dishonest attitude of trade union leaders were identified. The paper concluded that disunity and politicization of trade union are major obstacles for the development of strong and stable trade unions which is an integral part of cordial industrial relations. In addition, a strong and enlightened labour union is vital for good industrial relations system and help to promote the interest of labour union. It is recommended, among others, that unions should identify current trend in industrial relations and educate their members to anticipate for the changes brought about by environmental forces affecting industries. Trade unions should create a level playing ground for all members to take part in the decision making machinery of their unions. Union members should ensure that only qualified, tested and trusted leaders who are truly workers should be voted into offices both at the local, state and national level. In addition, union leaders should be properly trained and educated to know the basic labour and industrial laws of the country in order to plan their actions within the provisions of the laws. Trade unions should also provide for the adequate training of their members in order to give room for advancement of their members.